An Interior Point Method for Nonlinear Programming - Jahn, Johannes (Mathematical Methods of Operations Research, 1979)
In this paper an interior point method is presented for nonlinear programming problems with inequality constraints. On defining a modified distance function the original problem is solved sequentially by using a method of feasible directions. At each iteration a usable feasible direction can be determined explicitly. Under certain assumptions it can be shown that every accumulation point of the sequence of points constructed by the proposed algorithm satisfies the Kuhn-Tucker conditions. © 1979 Physica-Verlag.
UnivIS-Import:2015-03-05:Pub.1979.nat.dma.pama21.aninte